The Contribution of Leg Muscle Explosive Power and Strength to Long Jump Ability in USK Physical Education Students Class of 2022 - Muhammad Iqbal; Syamsulrizal Syamsulrizal; Mansur Mansur; Nofri Naldo; Dibra Farras Fahima; Iswanda Suryanullah (Journal on Education, 2024)
This study is entitled "The Contribution of Limb Muscle Explosive Power, Balance to Jumping Ability in Class XI Students of SMA Negeri 9 Banda Aceh Academic Year 2012/2013". Jumping is one of the athletic numbers whose achievement is influenced by components of physical condition such as Limb Muscle Explosive Power, Balance. This study aims to determine the contribution of Limb Muscle Explosive Power, Balance to jumping ability in grade XI students of SMA Negeri 9 Banda Aceh Academic Year 2012/2013 using purposive sampling techniques. The instruments used in this study were: (1) leg muscle explosive power, measured by standing broad jump test, (2) balance, measured using stork stand test, and (3) jumping ability measured by jumping test. Data is processed using statistical techniques in the form of calculation of mean value, standard deviation (SD) and correlational test. The results obtained were as follows: (1) there was a positive and significant relationship between the explosive power of the leg muscles and the ability to jump infection by (r = 0.49), (2) there was a positive and significant relationship between balance on the ability to jump infection by (r = 0.54) and (3) there was a positive and significant relationship between the explosive power of the leg muscles and balance on the ability to jump infection by (R_ (Y.X_1 X_2 ) = 0.61). The results of hypothesis testing show that Fcalculate = 6.52 ≥ Ftable = 3.44. Therefore, the explosive power of the limb muscles and balance have a significant contribution to the ability to jump infections.